Permanent revolution : the Reformation and the illiberal roots of Liberalism - Simpson, James, 1954- (The Belknap Press of Harvard University Press, 2019)
The proto-Liberalism of the late seventeenth century in England reverses all the central persuasions of illiberal evangelical religion of the early sixteenth century. Free-will, division of powers, non-literalist Biblical reading, aesthetics, theatricality: each reverses cardinal positions of Lutheran and Calvinist religion. How? Permanent Revolution argues that all revolutions take about 150 years to settle down. In the case of the Reformation in England, the first revolution (what Simpson calls "permanent revolution") was heady and radical. It was also ultimately unsustainable. In about 150 years it produced its opposite, the second Reformation which led to the Enlightenment. In our own times, the author says, liberals make a dangerous mistake when they do not understand that Evangelical fundamentalists descend from the same parent as themselves - the "permanent revolution" of the early Reformation. The core of the book is about the English Reformation and the archive is largely literary. Yet the political and intellectual ramifications exceed the remit of literary studies. The story of the proto-Enlightenment narrated here is not a story of secularist repudiation from outside. Instead, it is primarily a story of transformation and reversal of the Protestant tradition from within. The second Reformation (the one that became the Enlightenment) is less a secularist opponent of the first than its dissident younger sibling, driven and marked, if not scarred, by its older evangelical sibling and competitor.--